A ROMAN CATHOLIC PERSPECTIVE. - Tentler, Leslie Woodcock (Fides et historia, 2012)
The author reflects on the history of Christian confessional boundaries in the U.S., with a focus on the perspective of the Roman Catholic faith. The author emphasizes that the boundaries of the Catholic faith in the U.S. are more permeable in the 21st century than they were in the middle of the 20th century, as is evident through the increase of Catholics who marry across religious lines, as well as the decrease in the network of Catholic institutions. The author asserts that American pluralism helps to define the history of Catholicism in America.